Armed Forces Operational Command as a Crisis Management Center in the crisis management system of the Ministry of Defense - summary, conclusions and experiences - Stelmach Tomasz (2022)
The aim of this article is to present conclusions and experiences that have resulted of functioning of the Armed Forces Operational Command as the Crisis Management Center of the Ministry of National Defense. The author also focuses on the evolution of the military crisis management system.